2012
DOI: 10.1073/pnas.1202671109
|View full text |Cite
|
Sign up to set email alerts
|

Double knockout of pendrin and Na-Cl cotransporter (NCC) causes severe salt wasting, volume depletion, and renal failure

Abstract: The Na-Cl cotransporter (NCC), which is the target of inhibition by thiazides, is located in close proximity to the chloride-absorbing transporter pendrin in the kidney distal nephron. Single deletion of pendrin or NCC does not cause salt wasting or excessive diuresis under basal conditions, raising the possibility that these transporters are predominantly active during salt depletion or in response to excess aldosterone. We hypothesized that pendrin and NCC compensate for loss of function of the other under b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
140
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 33 publications
(60 reference statements)
5
140
1
Order By: Relevance
“…51,52 Moreover, NCC 2/2 mice exhibit an enhanced abundance of the bicarbonatechloride cotransporter pendrin, 53 which when deleted in NCC 2/2 mice, led to lethal salt wasting. 54 Consistent with the unchanged aldosterone levels in I-1 2/2 mice, we did not detect any evidence for an altered ENaC regulation. However, the pendrin protein abundance was found to be upregulated, which could have contributed to the compensated phenotype.…”
Section: Discussionsupporting
confidence: 72%
“…51,52 Moreover, NCC 2/2 mice exhibit an enhanced abundance of the bicarbonatechloride cotransporter pendrin, 53 which when deleted in NCC 2/2 mice, led to lethal salt wasting. 54 Consistent with the unchanged aldosterone levels in I-1 2/2 mice, we did not detect any evidence for an altered ENaC regulation. However, the pendrin protein abundance was found to be upregulated, which could have contributed to the compensated phenotype.…”
Section: Discussionsupporting
confidence: 72%
“…Because both β-and non-α/non-β ICs express the Cl/HCO 3 exchanger pendrin (39-41), we refer to them collectively herein as pendrin-positive ICs (PP-ICs) for simplicity. In addition to verifying the transcript abundance increase of pendrin (Slc264a4), which is activated in NCC KO mice (13,42), the profile revealed an increase in AE4 (Slc4a9), numerous V-type proton ATPase subunits (V0 subunit d2 and the V1 subunits B1, C2, and G3), and 2 different isoforms of carbonic anhydrase (CA2 and CA15). A comprehensive qPCR survey of IC transporters (Figtranscript levels was performed on kidney cortex samples from WT and SPAK KO mice using the Affymetrix whole-genome GeneChip Mouse Gene 1.0 ST Array, which represents all mouse genes and contains more than 28,000 total transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of this compensation is poorly understood. In NCC KO mice, activation of pendrin-mediated chloride absorption (13), ENaC (11,14), and NHE3-mediated sodium reabsorption (14) have been shown to contribute, but an integrated molecular understanding of adaptive responses to NCC inhibition has been wanting. To develop a better appreciation of the response, we sought to identify the gene networks in the kidney that are activated to drive NaCl reabsorption when NCC phosphorylation is compromised, as occurs in the absence of the STE20/SPS-1-related proline-alanine-rich protein kinase (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…This possibility is further supported by a recent study showing that double deletion of NCC and pendrin leads to massive sodium wasting, hypovolemia, and hypotension. 24 From the study of two independent mouse models of pseudohypoaldosteronism type II, 25,26 it has been concluded that increased electroneutral NaCl absorption by NCC is the main mechanism leading to this syndrome. Functional coupling of pendrin and Ndcbe mediates NCC-like activity.…”
Section: Discussionmentioning
confidence: 99%